TRENDS AND PREDICTIVE PATTERNS IN THE EVOLUTION OF THE FINANCIAL PERFORMANCE OF PUBLIC HEALTH OPERATORS THROUGH THE USABILITY OF MANAGEMENT ACCOUNTING - de Souza, Antônio Artur; Enes, Wilson Machado (Seven Editora, 2026)
This study analyzes trends and predictive patterns in the evolution of the financial performance of Brazilian Health Plan Operators (HPOs), emphasizing the role of managerial accounting usability as a decision-support and early-warning mechanism. The analysis is based on secondary data from the Brazilian National Agency for Supplementary Health (ANS), covering the period from 2017 to 2024, and organized into a balanced panel dataset. Methodologically, the study combines descriptive statistics, trend analysis, and panel data econometric models, enabling the identification of both temporal dynamics and unobserved heterogeneity among operators. The results reveal significant persistence in financial performance, particularly in return on assets, as well as a strong sensitivity to claims ratio (loss ratio) and managerial cost indicators. Variables associated with managerial accounting practices, such as operating margins, combined ratios, liquidity, and capital structure indicators, demonstrate substantial predictive power in anticipating future financial deterioration or recovery. The findings indicate that the effective use of managerial accounting information enhances the capacity of health plan operators to anticipate financial risks, improve cost control, and support strategic decision-making, especially in a highly regulated and cost-intensive environment. From a regulatory and managerial perspective, the study highlights the relevance of integrating managerial accounting indicators into continuous monitoring systems to strengthen the economic and financial sustainability of the supplementary health sector. DOI: https://doi.org/10.56238/sevened2026.008-055